PERAN KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. PERMATA ANUGERAH YALAPERSADA - Sindy Anggun Hariyanti; Leonard Adrie Manafe; Dhyah Wulansari (ITB AAS Indonesia Surakarta, 2023)
This study aims to provide a description and analysis related to the leadership role at PT. Permata Anugerah Yalapersada. The research method used in this study is qualitative with a descriptive approach. Primary data collection through interviews with eight company employees who became research informants. The results showed that the role of leadership in improving employee performance at PT. Permata Anugerah Yalapersada with leader performs interpersonal roles consisting of the role of the figurehead which is to represent the company, the role of the leader is to provide motivation and the role of liaison is to maintain communication with employees. The role of information consists of the role of the monitor, which is to receive information from various sources; the role of the disseminator such as always updating the latest information, the role of the spokesman is to convey information to outside parties. Decision making consists of the role of entrepreneurship namely providing ideas for job renewal, the role of handling disturbances as mediators in conflicts, the role of allocating resources by channeling funds transparently and the role of negotiators by participating in negotiations, the results show that the role of leaders has a significant effect on employee performance.